Indicators technology competitive activities of varying skill karate style «kyokushin» - Natalya Boychenko (Kharkiv State Academy of Physical Culture, 2014)
Purpose: to identify the main indicators of the art of competitive activity karate different qualifications style «kyokushin» and identify their differences. Material and Methods: analysis of video recordings of highly competitive activity karate; teacher observations; methods of mathematical statistics. Results: based on the analysis of video recordings of competitive activity created a model of technical preparedness karate qualifications. The differences in the technique of competitive activity karate different qualifications. Conclusions: it was found a series of karate techniques with different skills, their frequency of use and effectiveness. Confirmed that in the competitive fight karate qualifications dominated series techniques. It is found that the technique of competitive activity highly skilled athletes is very varied combinations strikes in series of two or three strikes and more.